Ambipolar charge-transport properties in 4, 10-dihalogenated anthanthrone crystals: a theoretical study1. Issue 9 (7th March 2015) - Tu, Zeyi; Huang, Xuri; Yi, Yuanping
<x xml:space="preserve">Abstract</x> Good ambipolar charge-transport characteristics have been revealed for the halogenated anthanthrone crystals by DFT and MD calculations.